Promoting access to assisted reproductive technology in Nigeria through the rights to benefits of scientific progress: an appraisal (2019)
The prevalence of infertility in Nigeria has risen gradually over the years to 30% in 2015. Assisted Reproductive technologies (ART) are therefore relevant to the Nigerian society where infertility is a major problem. The increase in prevalence of infertility has invariably led to increase in number of clinics offering fertility services. However, this increase in fertility clinics has not translated into increased access to ART services. Restricted access to medical treatment for infertility is one of the injustices obtainable in the field of reproductive medicine. Due to many factors, including financial incapacity, some people have easier access to treatment than others. Against this background, this paper explores the intersections between balancing rights to benefits of scientific progress of which ART is and promoting access to ART services for Nigerians through legislation. The paper leans on the utilitarian theory which promotes welfare for the greatest good of all. At present, the cost of obtaining standard procedures in ART range over One Million Naira ($3,290) which is way far above the means of an average Nigerian. This paper answers the question “should ART be regulated by legislation to provide comprehensive health care to allow individuals reap benefits of scientific progress or should it be left as a private sector driven concern where forces of demand and supply dictates its cost and accessibility?” This paper which gives further impetus to research on the legal framework for regulating ART in Nigeria concludes that infertility is a pervasive public health issue in Nigeria which exposes the sufferers to injustice and discrimination socially. Infringement of reproductive rights occurs when access to ART is not available, then via the instrumentality of law and policy, government could offer succor to this segment of the Nigerian society by ensuring cheaper access to ART services